Anomalous refraction control of mode-converted elastic wave using compact notch-structured metasurface. (27th March 2019) - Xu, Weikai; Zhang, Meng; Ning, Jinying; Wang, Wei; Yang, Tianzhi
Abstract: Elastic metasurfaces designed by assembling arrays of subwavelength anisotropic scatterers have shown great potential in the field of elastic and acoustic waves. Metasurfaces should be designed in consideration of simple configuration and manipulation efficiency. In this paper, we present a metasurface comprising compact notch structures for achieving anomalous refraction control of mode-converted elastic waves, for example, anomalous refraction, focusing, and self-acceleration. The proposed design is extremely compact and easy to implement and shows extraordinary wave-shaping ability. Numerical simulations well validate this design. The proposed results are potentially useful for applications such as in nondestructive examination, energy harvesting, and high-resolution lenses.